Gender Confirmation Surgery: Guiding Principles. Issue 6 (3rd May 2017) - Schechter, Loren S.; D'Arpa, Salvatore; Cohen, Mimis N.; Kocjancic, Ervin; Claes, Karel E.Y.; Monstrey, Stan
Abstract: Background: At this time, no formal training or educational programs exist for surgeons or surgery residents interested in performing gender confirmation surgeries. Aim: To propose guiding principles designed to aid with the development of formal surgical training programs focused on gender confirmation surgery. Methods: We use expert opinion to provide a "first of its kind" framework for training surgeons to care for transgender and gender nonconforming individuals. Outcomes: We describe a multidisciplinary treatment model that describes an educational philosophy and the institution of quality parameters. Results: This article represents the first step in the development of a structured educational program for surgical training in gender confirmation procedures. Clinical Implications: The World Professional Association for Transgender Health Board of Directors unanimously approved this article as the framework for surgical training. Strengths and Limitations: This article builds a framework for surgical training. It is designed to provide concepts that will likely be modified over time and based on additional data and evidence gathered through outcome measurements. Conclusion: We present an initial step in the formation of educational and technical guidelines for training surgeons in gender confirmation procedures.